A 500-mV, 124.11-nW first-order universal shadow filter based on multiple-input DDTAs - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz; Thanyaratsakul, Nattapong; Arbet, Daniel (My University, 2026)
This paper proposes a novel first-order multifunction filter capable of simultaneously realizing non-inverting and inverting low-pass, high-pass, and all-pass filter responses using multiple-input differential difference transconductance amplifiers (MI-DDTAs). The design leverages the shadow filter technique, enabling electronic tuning of the pole frequency across all filter responses through an external voltage-controlled amplifier. This approach offers enhanced flexibility and reconfigurability, making it highly attractive for adaptive analog signal processing. The MI-DDTA core is implemented using a multiple-input bulk-driven MOS transistor architecture, optimized for ultra-low-voltage and ultra-low-power operation. Designed in Cadence Virtuoso using the 65 nm TSMC CMOS (1P9M) process, the proposed MI-DDTA occupies a compact silicon area of 171 μm × 119 μm. Operating from a 500 mV supply, the shadow filter achieves a dynamic range of 55.9 dB for a 200 mVpp input signal, with total harmonic distortion limited to 1%. Owing to its exceptionally low bias currents, the shadow filter exhibits a total power consumption of only 124.11 nW, making it well suited for energy-constrained biomedical and IoT sensor applications, where low-frequency signal processing, compact implementation, and high energy efficiency are essential. To validate the proposed concept, a discrete prototype was also developed using MI-DDTA configurations built with LM13700 operational transconductance amplifiers. The experimental results confirm the expected filter behavior and demonstrate the feasibility of the proposed design in practical scenarios.
Keywords: Bulk-driven MOS transistor; First-order filter; Multiple-input MOS transistor; Operational transconductance amplifier; Shadow filter